Lakefront : public trust and private rights in Chicago - Kearney, Joseph D.; Merrill, Thomas W. (Cornell University Press, 2021)
"A history of how Chicago's lakefront, with its parkland and Lake Shore Drive, has come to be. Beginning with the mid-nineteenth century, this book considers both local and broader social, economic, and legal forces, with particular emphasis on the conflict between public and private rights"--